Inventarisasi Jenis dan Distribusi Habitat Rotan pada Hutan Dataran Tinggi dan Dataran Rendah di Kalimantan Selatan - Yudi Firmanul Arifin (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Rattans are spiny climbing palms in the Old World tropics and subtropics. Some species are the source of cane for the cane furniture industry in Indonesia. The large number of rattan species and their wide geographical range is matched by great ecological diversity. The restriction of rattan species to different climatic zones and altitudinal range suggests that these species may have precise climatic requirements and also altitudes. The research was conducted on upland and lowland of natural forest in South Kalimantan. The data collection used survey with transect method. Volume of rattans in upland forest was relatively lower than lowland forest. In altitudinal range in South Kalimantan, rattans were found from sea-level up to 870 m, the highest altitude record being held by Calamus javensis, Daemonorops micracantha, Calamus pilocellus, and Calamus sp. (rotan tunggal). While the lowest altitude record was occupied by Calamus trachycoleus. Rattans in natural forest require light intensity, humidity and temperature were 18– 65%, 60 – 70%, 28 – 33oC, respectively.